2020
DOI: 10.3390/biology9020033
|View full text |Cite
|
Sign up to set email alerts
|

From One Ejaculate to Another: Transference of Sperm Traits via Seminal Plasma Supplementation in the Ram

Abstract: Males can adjust sperm motility instantaneously in response to the perceived risk of sperm competition. The speed of this response suggests that sperm motility is regulated by changes in seminal plasma rather than changes in the sperm cells themselves. Hence, here we test whether inter-ejaculate variation in seminal plasma can be used to alter sperm quality prior to use in assisted reproductive technologies. We supplemented fresh ejaculates of Merino rams with seminal plasma collected from previous 'donor' eja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Indeed, seminal plasma is a complex mixture of molecules produced by the accessory sexual glands: seminal vesicles, prostate, bulbourethral glands, vas deferens, and epididymides [ 9 ]. Therefore, our findings can potentially be explained at least by (a) variation in the relative proportions (quantity) of different accessory sex gland secretions, (b) alteration of the molecular composition of any of these fluids, (c) or both [ 11 ]. Since proteins constitute the largest fraction of the seminal plasma and are regarded as a key modulator of sperm function [ 43 ], it seems likely that the above-mentioned differences between SP donors could be largely explained by sample-specific variation in SP proteome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, seminal plasma is a complex mixture of molecules produced by the accessory sexual glands: seminal vesicles, prostate, bulbourethral glands, vas deferens, and epididymides [ 9 ]. Therefore, our findings can potentially be explained at least by (a) variation in the relative proportions (quantity) of different accessory sex gland secretions, (b) alteration of the molecular composition of any of these fluids, (c) or both [ 11 ]. Since proteins constitute the largest fraction of the seminal plasma and are regarded as a key modulator of sperm function [ 43 ], it seems likely that the above-mentioned differences between SP donors could be largely explained by sample-specific variation in SP proteome.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that SP influences sperm performance, especially sperm swimming speed and viability [ 8 , 9 ]. Furthermore, two studies, performed on stallions and rams, have suggested that the effect of SP supplementation on sperm traits depends on the origin of both the SP and the sperm [ 10 , 11 ]. Despite these findings, the physiological significance of SP for fertilization success, especially in humans, has often been questioned as the exposure of sperm to SP seems to be unnecessary for the sperm fertilization capacity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of seminal plasma varies not only among species [22], but also among males and ejaculates within a male [23][24][25], demonstrating that semen composition is susceptible to environmental change. We know that variation in seminal plasma can regulate sperm phenotype because seminal plasma supplementation can be used to shift sperm traits such that they resemble the sperm traits of the donor ejaculate [26,27].…”
Section: Environmental Effects On Gamete Phenotypesmentioning
confidence: 99%
“…Growing evidence suggests that the sperm kinetics is regulated by SF composition. In this regard, Green et al concluded that SF from high‐quality semen could improve the sperm function in Ram models (Green et al., 2020). However, Makler et al.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggests that the sperm kinetics is regulated by SF composition. In this regard, Green et al concluded that SF from high-quality semen could improve the sperm function in Ram models (Green et al, 2020). However, Makler et al (1984) revealed no beneficial or detrimental effects of the exchange of SF between normozoospermic and oligoasthenozoospermic specimens on sperm motility.…”
mentioning
confidence: 99%